Jet propulsion engines. - Lancaster, Otis E. (High speed aerodynamics and jet propulsion, 1959)
Volume XII of the High Speed Aerodynamics and Jet Propulsion series. Partial Contents: Historical development of jet propulsion; basic principles of jet propulsion; analyses of the various types of jet propulsion engines including the turbojet, the turboprop, the ramjet, and intermittent jets, as well as solid and liquid propellant rocket engines and the ramrocket. Another section deals with jet driven rotors. The final sections discuss the use of atomic energy in jet propulsion and the future prospects of jet propulsion. Originally published in 1959. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.